Effect of Addition of Green Tea Extract (Camellia sinensis) in Egg Yolk Tris Diluter on Spermatozoa Quality in Bali Cattle (Bos sondaicus) After Freezing - Wijayanti, Ani; Suprayogi, Tri Wahyu; Prastiya, Ragil Angga; Hernawati, Tatik; Sardjito, Trilas; Saputro, Amung Logam; Amaliya, Anny; Sulistyowati, Deny (Universitas Airlangga, 2023)
This study aimed to determine the effect of adding 96% ethanol extract of green tea (Camellia sinensis) in egg yolk tris diluter on the quality of spermatozoa of Bali cattle (Bos sondaicus) after freezing. The samples were divided into four different treatment groups, which contained semen sample + 13% glycerol + each egg yolk tris diluter + green tea extract (P0) 0 mg/100 ml, (P1) 0,05 mg/100 ml, ( P2) 0,10 mg/100 ml, and (P3) 0,15 mg/100 ml. The variables observed included motility, viability, and spermatozoa abnormalities. Data were analyzed using OneWay ANOVA and continued with Duncan's test (p<0,05). The results showed that the P3 group had motility of 49,00 ± 2,15, viability of 61,92 ± 1,70, and abnormality of 4,24 ± 2,16 significantly compared to the other groups. In conclusion, the P3 group with the addition of 0,15 mg/100 ml of green tea could increase the motility, viability, and abnormal spermatozoa of Bali cattle.